Rancangan Produk Pemanfaatan Teknologi Informasi dan Komunikasi (TIK) Dalam Kursus - Lestari, Fitri Alia; Husna, Fitriatul; Safitri, Meliya; Hapsari, Novia Dwi; Sari, Nurmala (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
One of the problems that the Hazkia Education Center Course has is that the learning media used is less interesting or the learning media is still monotonous, which makes students less interested and easily feel bored and bored in the learning process. So, the goal to be achieved is to create a product design using ICT that will be useful for implementing the learning process at the Hazika Education Center Course. The methods used to collect data at the Hazika Education Center Course are observation and interviews. The results of the observations are that instructors at the Hazika Education Center must be able to utilize the Canva application platform to create attractive presentation designs which aim to ensure that students do not get bored easily during the learning process.